Potential impacts of lanthanum and yttrium on embryotoxicity assays with Crassostrea gigas - Moreira, Anthony (2020)
In the last decades, the production of electronic devices, which relies on rare earth elements (REE) such as yttrium (Y) and lanthanum (La), has increased exponentially, a pattern that should continue in the future. Besides the lack of raw materials, the growing generation of electronic waste (E-waste) and the REEs direct or indirect discharge into the environment raises worldwide concern. Mostly, given the scarcity of data about their toxicity to marine biota. In this study, a standardized toxicity test on oyster Crassostrea gigas embryonic development was performed to assess the impacts of La and Y. Lanthanum exerted significantly higher toxicity than Y, with median effect dose concentrations (EC50) of 6.7 to 36.1 µg L−1 (24 and 48 h) for La; and 147 to 221.9 µg L−1 (24 and 48 h) for Y. Higher toxicity of La was likely related to higher bioavailability of free ionic form (La3+). Comparison of toxicity thresholds with literature indicated that La is among the most toxic compounds to C. gigas embryos, while Y was ranked among compounds with intermediate toxicity. Overall, this work brings new insights into the potential implications of the widespread use of high-tech products, if appropriate management measures are not taken.